Extremes : reflections on human behavior - Dunning, A. J. (New York : Harcourt Brace Jovanovich, 1992)
Dutch cardiologist A. J. Dunning brings a wry wit and an impressive knowledge of art, literature, and religion to his essays on the sublime and the monstrous in society. He writes of Joan of Arc and Gilles de Rais, who were brought together in the service of their king and eventually burnt at the stake: one is a martyr, one as a pederast mass murderer. He compares a seventeenth-century nun's veneration of the heart with that of the first surgeons who performed heart transplants. He gives the clinical facts behind Gustav Mahler's fatal sore throat, Sigmund Freud's cocaine addiction, and Charlotte Corday's assassination of Marat in his bath. He tells of the practice in England of body-snatching for science, and of the practice in Italy of castrating young boys for music. He discusses parthenogenesis, the use of hormones in the search for eternal youth, and mystifying fatigue syndromes in different countries and generations. The invention of Braille. The satanic verse of Baudelaire. The atrocious eating habits of medieval saints and modern teenage girls. Informative, entertaining, preposterous tales - all documented, all true - of how unnatural human nature can be.
Extremes: A Mirror -- Extremes of the Heart. The Burning Heart. Heart Transplants. The Neurotic Heart. Soldier's Heart -- Extremes of Men and Knives. The Perfect Crime. The Anatomy Lesson. Eternal Youth. "Viva il Coltello" -- Extremes of Faith. Parthenogenesis. Heretics. Anorexia Religiosa -- Extremes of the Senses. A Taste for Cabin Boys. In the Land of the Blind. False Paradises.
Translation of: Uitersten.
"A Helen and Kurt Wolff book."
Includes bibliographical references (p. 203-207).
Keywords: Eccentrics and eccentricities; Characters and characteristics; Human behavior